(untitled) (Jurnal Pendidikan Islam, 2025)
Purpose – This study aims to examine the implementation of the Merdeka Curriculum in the subject of Islamic Religious Education (PAI) and Character Education at SMA Negeri 1 and SMA Negeri 2 Sibolga, focusing on the aspects of planning, implementation, and evaluation. It addresses the need for empirical evidence regarding the application of character-based curriculum practices in non-metropolitan areas, particularly within the context of contextual and transformative religious education. Design/methods/approach – Employing a qualitative descriptive approach and a multisite study design, this research involves participatory observation, in-depth interviews, and curriculum document analysis. Data were analyzed through a cross-site thematic approach to uncover convergent and divergent patterns in the implementation of the Merdeka Curriculum, including differentiated learning strategies and the application of project-based learning (P5). Findings – SMA Negeri 1 implemented a gradual approach through structured training, while SMA Negeri 2 adopted a more responsive model through independent teacher exploration and collective reflection. Teacher readiness, digital infrastructure, participatory leadership, and active student engagement emerged as key factors. Project-based learning and formative assessment enhanced student engagement and comprehension. Challenges included disparities in teacher understanding and low student learning autonomy. Research implications – The findings provide strategic guidance for schools to develop adaptive and participatory implementation of the Merdeka Curriculum through reflective training, technology integration, and learning approaches that are responsive to student needs.